Share value relational capital: Suggestions for the future and an assessment of past research in driving marketing performance - Samodro Bintang A.M Leonardus; Karona Cahya Susena; F Pambudi Widiatmaka; Sukrisno Sukrisno; Suherman Suherman (Journal of Innovation in Business and Economics, 2022)
This research aims to create a new theoretical framework that focuses on the impact of entrepreneurial orientation and relational capital stock value on the marketing performance of small and medium enterprises (SMEs) to gain a competitive advantage. This study involved 220 SMEs owners and used structural equation modeling to identify two effective strategies to improve SMEs marketing performance. Both strategies are the application of entrepreneurial orientation and utilization of share value relational capital.